Preimplantation Genetic Testing for Aneuploidy Could Not Improve Cumulative Live Birth Rate Among 705 Couples with Unexplained Recurrent Implantation Failure - Liu Y; Lan X; Lu J; Zhang Q; Zhou T; Ni T; Yan J (The Application of Clinical Genetics, 2024)
Yang Liu,1– 6,* Xiangxin Lan,1– 6,* Juanjuan Lu,1– 6,* Qian Zhang,1– 6 Tingting Zhou,1– 6 Tianxiang Ni,1– 6 Junhao Yan1– 6 1Center for Reproductive Medicine, Shandong University, Jinan, Shandong, 250012, People’s Republic of China; 2Key Laboratory of Reproductive Endocrinology of Ministry of Education, Shandong University, Jinan, Shandong, 250012, People’s Republic of China; 3Shandong Key Laboratory of Reproductive Medicine, Jinan, Shandong, 250012, People’s Republic of China; 4Shandong Provincial Clinical Research Center for Reproductive Health, Jinan, Shandong, 250012, People’s Republic of China; 5Shandong Technology Innovation Center for Reproductive Health, Jinan, Shandong, 250012, People’s Republic of China; 6National Research Center for Assisted Reproductive Technology and Reproductive Genetics, Shandong University, Jinan, Shandong, 250012, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tianxiang Ni; Junhao Yan, Center for Reproductive Medicine, Shandong University, Jinan, People’s Republic of China, Tel +0531-85651172, Email tianxiangni907@163.com; yyy306@126.comObjective: We evaluate whether next-generation sequencing (NGS)-based preimplantation genetic testing for aneuploidy (PGT-A) improves the cumulative pregnancy outcomes of patients with unexplained recurrent implantation failure (uRIF) as compared to conventional in vitro fertilization or intracytoplasmic sperm injection (IVF/ICSI).Patients and Methods: This was a retrospective cohort study (2015– 2022). A total of 705 couples diagnosed with uRIF were included in the study. 229 women transferred blastocysts based on morphological grading (IVF/ICSI) and 476 couples opted for PGT-A to screen blastocysts by NGS. Women were further stratified according to age at retrieval (< 38 years and ≥ 38 years). The primary outcome was the cumulative live-birth rate after all the embryos were transferred in a single oocyte retrieval or until achieving a live birth. Confounders were adjusted using binary logistic regression models.Results: Cumulative live-birth rate was similar between the IVF/ICSI group and the PGT-A group after stratified by age: IVF/ICSI vs PGT-A in the < 38 years subgroup (49.7% vs 57.7%, adjusted OR (95% CI) = 1.25 (0.84– 1.84), P = 0.270) and in the ≥ 38 years subgroup (14.0% vs 19.5%, adjusted OR (95% CI) = 1.09 (0.41– 2.92), P = 0.866), respectively. Nonetheless, the PGT group had a lower first-time biochemical pregnancy loss rate (17.0% vs 8.7%, P = 0.034) and a higher cumulative good birth outcome rate (35.2% vs 46.4%, P = 0.014) than the IVF/ICSI group in the < 38 years subgroup. Other pregnancy outcomes after the initial embryo transfer and multiple transfers following a single oocyte retrieval were all similar between groups.Conclusion: Our results showed no evidence of favorable effects of PGT-A treatment on improving the cumulative live birth rate in uRIF couples regardless of maternal age. Use of PGT-A in the < 38 years uRIF patients would help to decrease the first-time biochemical pregnancy loss and increase the cumulative good birth outcome.Keywords: preimplantation genetic testing for aneuploidy, unexplained recurrent implantation failure, cumulative live-birth rate, cumulative good birth outcome